Systemic Effects of Inflammation on Health during Chronic HIV Infection - Deeks, Steven G.; Tracy, Russell; Douek, Daniel C. (Immunity (Cambridge, Mass.), 2013)
Combination antiretroviral therapy for HIV infection improves immune function and eliminates the risk of AIDS-related complications but does not restore full health. HIV-infected adults have excess risk of cardiovascular, liver, kidney, bone, and neurologic diseases. Many markers of inflammation are elevated in HIV disease and strongly predictive of the risk of morbidity and mortality. A conceptual model has emerged to explain this syndrome of diseases where HIV-mediated destruction of gut mucosa leads to local and systemic inflammation. Translocated microbial products then pass through the liver, contributing to hepatic damage, impaired microbial clearance, and impaired protein synthesis. Chronic activation of monocytes and altered liver protein synthesis subsequently contribute to a hypercoagulable state. The combined effect of systemic inflammation and excess clotting on tissue function leads to end-organ disease. Multiple therapeutic interventions designed to reverse these pathways are now being tested in the clinic. It is likely that knowledge gained on how inflammation affects health in HIV disease could have implications for our understanding of other chronic inflammatory diseases and the biology of aging.